Innovation and Reform in Course Planning, Teaching, and Assessment: The CEFR in Canada and Switzerland, A Comparative Study - Piccardo, Enrica; North, Brian; Maldina, Eleonora (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2019)
Change and innovation in education require carefully thought-through procedures as well as time, and benefit both from exchanges of expertise between contexts and from quality assurance (QA) processes. A key document that stimulates change in planning, teaching, and assessment is the Council of Europe’s (2001) Common European Framework of Reference for Languages (CEFR). However, its innovation potential in language education has been affected by a lack of impact studies and QA procedures. This article reports on the QualiCEFR study, which aims to encourage a culture of QA in relation to planning, teaching, and assessment and to identify promising practices in those processes. The study compared CEFR implementation in Switzerland and Canada employing a mixed-methods design and a QA approach, thematically analyzing data from over 40 interviews. Results have helped to inform the development of an online tool produced in a sister project of the European Centre for Modern Languages (ECML).